Effect of Talent Management and Employee Engagement on Turnover Intention with Employee Retention Mediation - Indra Setiawan; Satrio Prasojo (Kusuma Negara Business School, 2021)
In facing the current business competition, the company must also have an advantage in order to be able to survive and develop among its competitors. Turnover Intention is one of the problems that are often faced by companies or organizations. The cause of high turnover in the company due to the desire to move is related to negative attitudes from employees, such as lack of satisfaction and commitment to the company. This study aims to determine the effect of Talent Management and Employee Engagement on Turnover Intention with the mediating variable Employee Retention Case Study PT. Yamada Indonesia Plant 2nd Factory. The sampling technique in this study is based on the employee population by means of total sampling or census samples with a sample of 71 employees at PT. Yamada Indonesia Plant 2nd Factory. Data analysis method used in this study with the help of SmartPLS. The results of this study indicate that Talent Management has a negative and significant influence on Turnover Intention, Employee Engagement has an influence on Turnover Intention, Employee Retention has an influence on Turnover Intention, Talent Management has an influence on Employee Retention, Employee Engagement has an influence on Employee Retention, Employee Retention can mediate Talent Management on Turnover Intention and Employee Retention can mediate Employee Engagement on Turnover Intention.